Research on Mutual Synergy of Antiwear Additives in Lithium Complex Grease - Yu,W; Zhang,C; Dong,Y; Reddyhoff,T (Tribology Transactions, 2016)
In recent years, with the enhancement of environment awareness, there has been a progressive reduction in permitted phosphorus and sulfur levels in lubricants. Sulfur and phosphorus are the most important elements of antiwear additives. Because of the reaction between additives, less mass of additives may have the same wear reducing properties when used together. However, there is uncertainty regarding the optimum amount and ratio of these additives. In this article, the influence of five kinds of antiwear additives—sulfurized olefin cottonseed oil (T405), sulfurized isobutylene (SIB), tricresyl phosphate (TCP), molybdenum dialkyl dithiophosphates (MoDTC), zinc dialkyl dithiophosphate (ZDDP), and their combination—on lithium complex grease have been studied by single-factor and orthogonal experiments. The single-factor tests show that T405 and SIB work well under low temperature, whereas TCP and MoDTC work well under higher temperature; ZDDP are multifunctional additives. It was proved that base grease has better antiwear properties at 150 than at 75°C. Additionally, sulfurized additives T405 and ZDDP and phosphate agent TCP could react better with lithium complex grease than the additives that have the same functional group. Furthermore, the results of orthogonal experiments show that the abrasion resistance of lithium complex grease is optimally best when T405, TCP, and ZDDP are blended with a ratio of 2:2:1. In addition, a synergistic effect between T405 and TCP is observed at ratios between 1:1 and 2:1. The morphology and element composition of the worn surfaces are examined by scanning electron microscopy (SEM) and energy-dispersive spectrometry (EDS). Based on the two kinds of technology, the friction and wear mechanism of additives also have been studied.